Detention: Effect or Cause of Deviance? An Analysis of the Arguments Provided by Romanian Inmates - Goga, Cristina Ilie (European Scientific Journal, ESJ, 2017)
The sociology of deviance places great importance on the causes of delinquency. A question always arises: why, in the same context, some people commit crimes and others do not? The first part of the article is based on the analysis of the causal theories of deviance, showing the views of some famous authors such as Cesare Lombroso, Edwin Sutherland, Michel Foucault or Erving Goffman. The second part of the paper presents the results of a sociological survey conducted in a Romanian penitentiary and analyses the prisoners’ perspective on the causes that led them to commit those delinquent acts and also their perception of the influence that the detention system has on their personal development and on the risks that incarceration incurs.